Improving nurses' performance in the safe handling of antineoplastic agents: a quasi-experimental study - A Nouri; M Seyed Javadi; E Iranijam; M Aghamohammadi (BMC, 2021)
Abstract Background The safe and standard handling of antineoplastic drugs can reduce the effects of occupational exposure and promote safe behaviors in nurses. Thus, the present study aimed to determine the effects ofstandard guidelines education on the safe handling of antineoplastic drugs among oncologynurses in Ardabil, Iran. Methods Thequasi-experimental study with a one-group pretest-posttest design was performed among 32 nursesworking in the oncology wards of two educational hospitals in Ardabil city, during 2020. Allthe nurses in the wards who met the inclusion criteria participated in the study. The data were collectedby usinga demographic information form and nurses'knowledge assessment questionnaire regardingthe standard guidelines for working with antineoplastic drugs, and a standard checklist for examiningtheir performance in this regard. Subsequently, they were analyzed by descriptive (mean and standard deviation) and inferential statistics (t-test)and Pearson's correlation coefficient) in SPSS 22. Results The mean and standard deviation of the knowledge and performance scores of the oncology nurses was59.56±6.41and 18.96±2.54 respectively, which changed to 66±4.82 and 32.03±2.45 respectively three months after training. The results of the t-test represented a statistically significant difference between the level of knowledge and performance before and after the intervention (P=0.001). Conclusions Based on the results, the standard guidelines education improved the nurses' knowledge and performance on the safe handling of antineoplastic drugs in the chemotherapy wards. Therefore, it is advised to increase the awareness of the oncology nurses in this regard in the planning and policy-making ofhealthcare centers.